Society and State in Ancient Mesopotamia. Sumer - Diakonoff, I. M. (1959)
I: In early dynastic Sumer: 1. Area of the Sumerian “citystate” and the temple area – 2. Sumerian community and the social structure of the population – 3. Structure of the early Sumerian state — II: History of the Sumerian society and state: 1. Military democracy and the aristocratic oligarchy – 2. Rise of despotism and the struggle for its consolidation – 3. Despotic state under the IIIrd Dynasty of Ur; in Russian with English summary.